Manipulating Nutritional Conditions and Salinity‐Gradient Stress for Enhanced Lutein Production in Marine Microalga Chlamydomonas sp. Issue 4 (23rd January 2019) - Xie, Youping; Lu, Kongyong; Zhao, Xurui; Ma, Ruijuan; Chen, Jianfeng; Ho, Shih‐Hsin
Abstract : Marine microalgae has great potential for lutein production with the advantage of saving fresh water resource. Thus, marine microalga Chlamydomonas sp. JSC4 is investigated as a potential lutein producer in this study. The medium types, nitrate‐N and sea salt concentration are individually investigated to promote the cell growth rate and lutein production of JSC4. In Modified Bold Basal 3N medium, cell growth and lutein content are optimal at the nitrate‐N concentration of 1000 mg L −1 and sea salt concentration of 2%. In addition, an innovative salinity‐gradient strategy is operated to dramatically enhance biomass productivity (560 mg/L/d) and lutein content (3.42 mg g −1 ), resulting in the optimal lutein productivity (1.92 mg/L/d). Overall, this study clearly demonstrates that salinity is a significant inducer of lutein accumulation by strain JSC4 and that lutein production can be successfully optimized using the salinity‐gradient strategy, which is beneficial for the outdoor large‐scale lutein production in the future. Abstract : Marine microalga Chlamydomonas sp. is investigated as a potential lutein producer. The medium types, nitrate‐N and sea salt concentration are individually investigated to promote the cell growth rate and lutein production. Moreover, this study demonstrates that salinity is a significant inducer of lutein accumulation and that lutein production can be successfully optimized using the salinity‐gradient strategy, which is beneficial for the outdoor large‐scale lutein production.